2007
DOI: 10.4103/0022-3859.37509
|View full text |Cite
|
Sign up to set email alerts
|

Miliary tuberculosis in human immunodeficiency virus infected patients not on antiretroviral therapy

Abstract: Background: An increase in tuberculosis (TB) incidence has been associated with human immunodeficiency virus (HIV). Aims: To describe the clinical characteristics and treatment outcome of patients with HIV and miliary TB treated with short-course intermittent chemotherapy in the absence of access to highly active antiretroviral therapy (HAART). Settings and Design: Prospective study of HIV infected adults re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The case fatality rate in our hospital was 21%, which is higher than that reported from Senegal and Morocco [5], [6] but lower than that reported from Mali [4]. This high mortality rate could be explained by the delay in consultation, poor health resources, and impact of HIV infection [16]. Similar findings were reported from Burkina Faso [17].…”
Section: Discussionsupporting
confidence: 66%
“…The case fatality rate in our hospital was 21%, which is higher than that reported from Senegal and Morocco [5], [6] but lower than that reported from Mali [4]. This high mortality rate could be explained by the delay in consultation, poor health resources, and impact of HIV infection [16]. Similar findings were reported from Burkina Faso [17].…”
Section: Discussionsupporting
confidence: 66%
“…However, since the 1980s a changing epidemiological trend has been observed and miliary TB is increasingly being recognized in adults also. Two peaks are evident, one involving adolescents, young adults and another later in life among elderly individuals [2], [3], [4], [5], [14], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50]. This epidemiological change has been thought to be due to global pandemic of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), increasing occurrence of organ transplantation, use of immunosuppressive drugs including anti-TNF-α, chronic hemodialysis program, among others.…”
Section: Epidemiologymentioning
confidence: 99%
“…In pediatric as well as adult series [2], [3], [4], [5], [14], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], male gender seems to be more frequently affected by miliary TB. In some adult series on miliary TB [14], [22], [34], [39] a female preponderance has been documented.…”
Section: Epidemiologymentioning
confidence: 99%
“…A study carried out in India showed that 45% of HIV-positive patients with miliary TB had positive AFB smear sputum microscopy results and 61% had positive cultures; however, neither the number of samples, the type of sample (spontaneous or IS) nor the radiological findings were described. (25) This finding has a practical issue, if we consider these patients at a potential risk of transmitting the disease and therefore requiring isolation.…”
Section: Discussionmentioning
confidence: 99%